Application of metamaterials in antenna technology (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The purpose of this article is to investigate the application of metamaterials in antenna technology. The possibility of using the metamaterial as a substrate with DNG material was assessed. To determine the characteristics of antennas, the properties of the interface between free space and artificial material are considered. A variety of metamaterial-based antenna systems can be used to support surveillance sensors, communications links, navigation and control systems. In addition to miniaturization, new antenna configurations have a wide range of applications, from RF devices to optical devices. Other combinations of metamaterial antenna subsystems are being explored for various devices. Based on the results of the analyses, a high-impedance surface based on metamaterials was proposed.
Keywords: metamaterial, high-impedance surface, efficiency, antenna technology, metamedium